2016
DOI: 10.1126/science.aaf4759
|View full text |Cite
|
Sign up to set email alerts
|

Cratering on Ceres: Implications for its crust and evolution

Abstract: Thermochemical models have predicted that Ceres, is to some extent, differentiated and should have an icy crust with few or no impact craters. We present observations by the Dawn spacecraft that reveal a heavily cratered surface, a heterogeneous crater distribution, and an apparent absence of large craters. The morphology of some impact craters is consistent with ice in the subsurface, which might have favored relaxation, yet large unrelaxed craters are also present. Numerous craters exhibit polygonal shapes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
188
0
11

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 147 publications
(209 citation statements)
references
References 64 publications
10
188
0
11
Order By: Relevance
“…Comparisons of d/D for Ceres' largest craters to finite element simulations of viscous relaxation indicated that most had experienced negligible relaxation (Bland et al, ) and suggested that Ceres was less ice‐rich than anticipated. At the same time, morphological analysis indicated that the transition from simple to complex craters on Ceres occurred at a d/D consistent with icy Saturnian satellites and inconsistent with rocky bodies (Hiesinger et al, ). Together, these two lines of analysis indicated that Ceres' crust (roughly Ceres' outer 40 km; Fu et al, ) is composed of a material that behaved like ice on short timescales/high strain rates and like rock on long timescales/low strain rates.…”
Section: Resultsmentioning
confidence: 99%
“…Comparisons of d/D for Ceres' largest craters to finite element simulations of viscous relaxation indicated that most had experienced negligible relaxation (Bland et al, ) and suggested that Ceres was less ice‐rich than anticipated. At the same time, morphological analysis indicated that the transition from simple to complex craters on Ceres occurred at a d/D consistent with icy Saturnian satellites and inconsistent with rocky bodies (Hiesinger et al, ). Together, these two lines of analysis indicated that Ceres' crust (roughly Ceres' outer 40 km; Fu et al, ) is composed of a material that behaved like ice on short timescales/high strain rates and like rock on long timescales/low strain rates.…”
Section: Resultsmentioning
confidence: 99%
“…This feature does not correlate with the color ratio composite maps (Williams et al, ) nor with maps of spectral features (McCord & Zambon, ). However, this feature broadly corresponds to a zone of low crater density (Hiesinger et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Smooth circumcrater areas correspond to ejecta blankets covering preexisting heavily cratered terrains. The areas of subdued circumcrater roughness were previously identified as low‐crater‐density areas in Hiesinger et al (). This behavior is notably different from that of lunar, Martian, and Mercurian crater ejecta.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously used the asteroid‐derived cratering rate, which relies on current best knowledge of the asteroid size‐frequency distribution and collision rates (e.g., Bottke et al, ; Marchi et al, ). Another model describing the impact cratering rate on Ceres is the lunar‐derived model (LDM), which takes the known crater chronology for the Moon and extrapolates it to Ceres (Hiesinger et al, ).…”
Section: Resultsmentioning
confidence: 99%